PERANCANGAN UI/UX GENERAL MEDICAL CHECK-UP PADA PERUSAHAAN TAMBANG X DENGAN METODE SURVEI DAN INTERVIEW - Eka Samsiati Putri; Firma Syahrian (Jurnal Ilmiah Teknologi Infomasi Terapan, 2024)
The mining industry, a crucial component of the world economy, is inextricably linked to occupational safety hazards and serious health dangers. Effective work safety measures are critical in sustaining worker health, one of which is routine Medical CheckUp (MCU). Mining Company X's MCU installation has been completed, but operating conditions and reporting remain manual, and inspection procedures and job eligibility assessments are inconsistently implemented. As a result, it is vital to digitize the MCU process using the General Medical Check-Up (GeMCU) system. This final project implements the survey and interview method, with testing conducted utilizing System Usability Scale (SUS) and User Acceptance Test (UAT), to assess user usability and satisfaction. The test findings showed that the average score of the System Usability Scale (SUS) test was 75.25 with the "Good" category, and the average score of the User Acceptance Test (UAT) test in each element was 90% for the design aspect, 84% for the user-friendliness aspect, and 82% for the efficiency aspect. Thus, the results of this test can be used as a basis for the feasibility of GeMCU UI/UX design by mining company X.